ANALISIS IMPLEMENTASI PRINSIP PENGEMBANGAN KURIKULUM PAI TERHADAP EFEKTIVITAS PEMBELAJARAN DI PERGURUAN TINGGI - Dhini Maulidatul Isnaini; Indah Ayu Febriana; Risma Wati Agustina; Muhammad Fadlullah; Ma’mun Hanif Hanif (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study examines how the application of Islamic Religious Education (IRE) curriculum development principles impacts the quality of education in higher education institutions. This research is grounded in the need to develop a curriculum that keeps pace with the times while upholding Islamic values in the learning process. PAI instruction in higher education still faces many challenges. These include theoretical teaching methods, limited use of technology, and a lack of student participation in the learning process. The objective of this study is to examine how curriculum development principles are applied and how this affects the effectiveness of PAI instruction in higher education. The method used was a qualitative descriptive approach involving a literature review of relevant references and scientific journals on curriculum development and Islamic Education (PAI) instruction. The results of the study indicate that the application of the principles of relevance, flexibility, continuity, effectiveness, efficiency, and practicality in the PAI curriculum can improve the quality of learning when supported by innovative teaching methods, instructor expertise, and student resources. Furthermore, it has been demonstrated that contextual, reflective, and project-based learning approaches can increase student participation and strengthen their religious and social attitudes. Thus, continuous curriculum development is necessary to ensure that PAI instruction not only focuses on cognitive aspects but also fosters students who are critical, adaptable, religious, and prepared to face the challenges of the modern era.